Developing Psychosocial Support for Medical Students: A Review: Addressing the Challenges of Medical Students' Psychosocial Well-being (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Today, we live in a time of knowledge explosion, and the availability of healthy and qualifiedhuman resources has become the most important factor in every community's success. The areas ofmedical school student life, but none have examined the whole student experience. This strategy isintended to identify students' potential stressors and address them at the appropriate time. Teachersand mentors who reacted favorably agreed that these students are the prospective physicians oftomorrow and that, in addition to academic and clinical training, they should be provided withnecessary psychological aid to ensure their well-being. Medical schools must explore how to assiststudents who are still upset for various reasons, including a lack of resources. Poor time managementof daily activities, lifestyle, understanding of the medical profession and related expectations, studyhours and the library's quality lecture, use of social networking sites, diet pattern, sleeping habits, andmode of entertainment were all assumed variables based on available studies in this field. Manystudents are left unattended due to their own behavior complexities, hesitation, poor English, pooradjustment with studies, 24 poor management of time and daily routine, suddenly becoming involved inirrelevant activities for example, emotional relationship, feeling of discrimination (academic andfinancial), poor interest in extra-curricular activities, indecisiveness and future uncertainties, Everycitizen's right to education and health, including students at India's most prominent medical, dentistry,and paramedical colleges, are basic rights. In this paper discuss the various type of DevelopingPsychosocial Support for Medical Students.